2020
DOI: 10.1037/dev0000879
|View full text |Cite
|
Sign up to set email alerts
|

Testing three hypotheses about effects of sensitive–insensitive parenting on telomeres.

Abstract: Telomeres are the protective DNA-protein sequences appearing at the ends of chromosomes; they shorten with each cell division and are considered a biomarker of aging. Shorter telomere length and greater erosion have been associated with compromised physical and mental health and are hypothesized to be affected by early life stress. In the latter case, most work has relied on retrospective measures of early life stressors. The Dutch research (n ϭ 193) presented herein tested 3 hypotheses prospectively regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 115 publications
(180 reference statements)
2
18
1
Order By: Relevance
“…Among important factors affecting life-course TL dynamics, there are developmental experiences such as intrauterine unfavorable events (Entringer et al, 2018;Habibi et al, 2020), TL at birth (Gorenjak et al, 2020), as well as early life adversity (family's low socioeconomic status, childhood neglect or abuse, etc.) (Belsky and Shalev, 2016;Ridout et al, 2018;Beijers et al, 2020). This is all the more important that early-life exposures can likely affect health status and longevity not only in directly exposed individuals but also in their offspring (Vaiserman et al, 2017).…”
Section: Genetic and Environmental Determinants Of Tlmentioning
confidence: 99%
“…Among important factors affecting life-course TL dynamics, there are developmental experiences such as intrauterine unfavorable events (Entringer et al, 2018;Habibi et al, 2020), TL at birth (Gorenjak et al, 2020), as well as early life adversity (family's low socioeconomic status, childhood neglect or abuse, etc.) (Belsky and Shalev, 2016;Ridout et al, 2018;Beijers et al, 2020). This is all the more important that early-life exposures can likely affect health status and longevity not only in directly exposed individuals but also in their offspring (Vaiserman et al, 2017).…”
Section: Genetic and Environmental Determinants Of Tlmentioning
confidence: 99%
“…Numerous studies support the fact that ELS and CT are independently associated with both shorter telomere length or increased mtDNA copy number in adults [102,136,137]. Interestingly, such studies have allowed a better differentiation of the biological pathways leading to OXS in adulthood and offered evidence that type and intensity of CT [138], age of exposure [139], memory of the trauma [140], and gender [141] all play a very important modulating role, while, for example, intensive parenting may play a biologically buffering role on telomere erosion effects of CT/ELS [142].…”
Section: Oxs In Human Els Studiesmentioning
confidence: 99%
“…Further, to gain a better understanding which neurobiological mechanisms underlie increased environmental susceptibility in individuals born with larger brain volumes in terms of normal and pathological development, controlled experimental studies in animal models aiming at manipulating neurodevelopmental processes that will affect neonatal brain size are warranted. Interestingly, it has been proposed that the prenatal environment may program postnatal susceptibility to environmental conditions including parenting ( Beijers et al, 2020 ; Hartman and Belsky, 2018 ), with stress-sensitive neurotrophic factors during fetal brain development potentially playing a role ( Hellström et al, 2016 ). We have previously reported that maternal childhood maltreatment was associated with smaller neonatal brain size ( Moog et al, 2018 ), a phenotype that we here observed to underlie lower sensitivity to parenting quality.…”
Section: Discussionmentioning
confidence: 99%